Gamelan Jawa Sebagai Sarana Dakwah Islam - Irma Syabana, Natasya; Nisa', Khoirun (Postgraduate Studies UIN Sunan Ampel Surabaya, 2024)
Gamelan is a musical ensemble that often features instruments such as metallophones, xylophones, drums, and gongs. This gamelan music ensemble consists of several musical instruments which, when played together, create an instrument. Musicians can enjoy gamelan music just by listening to the sound, or use gamelan as an accompaniment in other artistic performances. The peculiarity of gamelan is that its sound is not visual, so it is easy to combine with various other types of art. Gamelan is said to have been created by Sang Hyang Guru, a god who ruled all of Java, and who had a palace on Mount Mahendra in the Madangkamalan region or what is now known as Mount Lawu. Initially, gamelan was created in the form of a gong which was used to summon the gods.